Arrival declaration forms. A new gateway for mapping migration to Luxembourg - Venken, Machteld; Sauer, Arnaud (Frontiers in Human Dynamics, 2022)
Since the late 19th century, foreigners moving to Luxembourg have been required to declare their residency at the local municipality upon arrival. New digital technologies have made it possible to analyze the wealth of information contained in arrival declaration forms. This article offers a first digital analysis of a selection of these sources for the municipalities of Dudelange and Differdange in the mid-1920s. This was a pivotal period during which migratory flows to the Minett region, one of Europe’s most dynamic industrial regions characterized by its iron mines and steelworks, were increasing and diversifying. Using a digital hermeneutic approach, the article evaluates the choices, opportunities and difficulties involved in using these sources within the virtual environment nodegoat. It presents the new insights gained by visualizing migration paths and settlement patterns: that unmarried declarants were more mobile than married migrants, that the owner of a café and hostel (café-pension) in Dudelange hosted Italian migrants from his place of birth, and that social networks among family members and friends were also active on the road, with family members, for example, waiting for each other in the French transit town of Trieux. We end our article by identifying avenues for further research.